International Capital Markets, 1998. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1998)
This year's capital markets report provides a comprehensive survey of recent developments and trends in the advanced and emerging capital markets, focusing on financial market behavior during the Asian crisis, policy lessons for dealing with volatility in capital flows, banking sector developments in the advanced and emerging markets, initiatives in banking system supervision and regulation, and the financial infrastructure for managing systemic risk in EMU.